2018
DOI: 10.1371/journal.pone.0196259
|View full text |Cite
|
Sign up to set email alerts
|

Virological and immunological failure of HAART and associated risk factors among adults and adolescents in the Tigray region of Northern Ethiopia

Abstract: BackgroundHuman immunodeficiency virus/Acquired immunodeficiency syndrome associated morbidity and mortality has reduced significantly since the introduction of highly active antiretroviral therapy. As a result of increasing access to highly active antiretroviral therapy, the survival and quality of life of the patients has significantly improved globally. Despite this promising result, regular monitoring of people on antiretroviral therapy is recommended to ensure whether there is an effective treatment respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
78
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(123 citation statements)
references
References 54 publications
(123 reference statements)
28
78
7
Order By: Relevance
“…The finding of 11% VF in this study was lower than those studies from a number of lower than the figures from a number of low and middle income countries (10,17,(23)(24)(25)(26). The 88.1% VLS in this study is consistent with the finding of a previous cross-sectional study from Ethiopia in Tigray region which reported that TF was 11.5% while it is higher than a figure from a study conducted in Gondar(4.5%) (23,27). Despite having an overall high virological success, the level of virological suppression achieved in the subsequent viral load measurement among the patients with initial VF was low (35.3%).…”
Section: Discussionsupporting
confidence: 85%
“…The finding of 11% VF in this study was lower than those studies from a number of lower than the figures from a number of low and middle income countries (10,17,(23)(24)(25)(26). The 88.1% VLS in this study is consistent with the finding of a previous cross-sectional study from Ethiopia in Tigray region which reported that TF was 11.5% while it is higher than a figure from a study conducted in Gondar(4.5%) (23,27). Despite having an overall high virological success, the level of virological suppression achieved in the subsequent viral load measurement among the patients with initial VF was low (35.3%).…”
Section: Discussionsupporting
confidence: 85%
“…Studies found through databases search were done between 2005 and 2016. Eight of the studies were conducted in the Amhara region, whereas five in Addis Ababa [13,[21][22][23][24], three in Oromia [18,25,26], one in Tigray [14], and one in SNNPR [27]. Three studies were done by case-control study design [24,28,29], four studies by cross-sectional [14,[30][31][32], and eleven by cohort study design [13, 15-18, 21-23, 25-27].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Eight of the studies were conducted in the Amhara region, whereas five in Addis Ababa [13,[21][22][23][24], three in Oromia [18,25,26], one in Tigray [14], and one in SNNPR [27]. Three studies were done by case-control study design [24,28,29], four studies by cross-sectional [14,[30][31][32], and eleven by cohort study design [13, 15-18, 21-23, 25-27]. Ten studies were done on adult population [13, 16, 17, 21, 23-25, 28, 29, 32], six on children [15,18,22,26,27,31], and two on all age group [14,30] (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations